2012
DOI: 10.1088/0022-3727/45/45/455002
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic properties of Ba2+ and Gd3+ co-doped bismuth ferrite: magnetic, ferroelectric and impedance spectroscopic analysis

Abstract: Enhanced magnetoelectric coupling is observed in bismuth ferrite samples, co-doped with non-magnetic Ba and magnetic Gd ions replacing Bi and Fe, respectively. Distortion in Fe–O octahedra has a significant effect on the magnetic properties of the samples. Ferromagnetic signature is found to increase significantly in the co-doped samples with respect to the only-Gd-doped sample both at 80 and 300 K. The co-doped samples show enhanced electric polarization as well as the highest resistivity at room temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(42 citation statements)
references
References 52 publications
5
36
0
Order By: Relevance
“…It was also reported that this behavior can be also caused by magnetodielectric effect which is principally due to magnetoresistive response of the multiferroic sample. 73,74 It confirms that active conducting (resistive) grain boundaries are responsible for the large magnetic-dielectric response and dielectric anomaly in the vicinity of T N .…”
Section: G Impedance and Modulus Spectroscopymentioning
confidence: 62%
“…It was also reported that this behavior can be also caused by magnetodielectric effect which is principally due to magnetoresistive response of the multiferroic sample. 73,74 It confirms that active conducting (resistive) grain boundaries are responsible for the large magnetic-dielectric response and dielectric anomaly in the vicinity of T N .…”
Section: G Impedance and Modulus Spectroscopymentioning
confidence: 62%
“…[34][35][36] As shown in Table I, φ increase significantly with Ba-doping which is analogous with previous investigation. 37 The change in bond angle modifies the tilting angle of FeO 6 octahedron which might suppress the spiral spin structure and hence outset net magnetization in BBFO nanoparticles. On the contrary, according to Goodenough-Kanamori rule the AFM superexchange interaction between two magnetic ions with partially filled d orbital increases with increasing bond angle, φ and is strongest when φ = 180 o .…”
Section: Room Temperature M-h Hysteresis Loops Of Nanocrystalline Bfomentioning
confidence: 99%
“…Also the systemic research on complex impedance and ME coupling of BST-BFO ceramics is not published yet. On the other hand, substitution of rare-earth elements in the B-site of BFO perovskite is rare but improved magnetic properties are expected by the substitution of magnetically active rare-earth atoms [11].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, enhanced magnetic properties are noticed for the case of Fe-deficient Gd doped BFO [12]. Due to the 4 difference of magnetic moment of Fe 3+ (μ eff = 5.92 µ B ) and Gd 3+ (μ eff =7.63 µ B ) and ionic radii between the cations, there is a significant lattice distortion and hence improve magnetic properties [11]. It is expected that the magnetically active rare earth atom Dy will play the same role.…”
Section: Introductionmentioning
confidence: 99%